EVALUASI PELAKSANAAN METODE STORYTELLING DALAM PEMBELAJARAN ANAK USIA DINI - Yusra (Majelis Pendidikan Aceh, 2022)
Storytelling method is one of method that was often used in early childhood learning. The purpose of this study is to evaluate the implementation of storytelling method in early childhood learning. This study used qualitative method through descriptive approach which is located in Ar-Raihan Kindergarten, Bireuen Regency, Aceh. This study selected three teachers as research sample. Data collection technique used interview, while the process of data analysis was carried out through recording and transcribing then was narrated in discussion by using coding technique. The discussion is narrated in three stages, namely understanding, teaching techniques and implementation. The result of understanding clarified that teachers understood on the storytelling method that was applied in learning process. In teaching technique, those teachers have chosen story books according to the topic and sub-topic based on the lesson plan. While at the implementation, teachers set rules in order that classroom condition was conducive and fun, and they used media which can help to achieve storytelling goal in order to develop children's early literacy, and children are able to apply values of stories in daily life.